(untitled) (Al-Academy, 2025)
There is a reciprocal relationship between humans and the natural environment (place), as the environment contributes to shaping human behavior, imprinting his thoughts, identity, physiology, and determining his philosophy, myths, religions, and architecture. At the same time, humans contribute to adding human characteristics to the environmental space. Contemporary art is a powerful expressive medium that reflects the relationship between humans and the natural environment. Although many artists have addressed the themes of the environment and the human connection to it, there is a shortcoming in representing concepts of adaptation to different environmental conditions and studying the psychological space of humans. With the development of societies, contemporary art has gained an increasing role in exploring the deep links between humans and nature. This research examines the role of contemporary art in embodying the human connection to the natural environment, its reflections in human behavior, and the ways humans adapt to living spaces associated with the environment. It also studies the impact of the environment on human behavior and explores how art contributes to enhancing environmental awareness and reshaping human perceptions of their living spaces. The research relied on the descriptive-analytical method to analyze a set of contemporary artworks that addressed the themes of the natural environment and humans. A purposive sample of 23 artworks from different artistic fields and historical periods was analyzed, concerning human behavior within the natural environment and how humans adapt to living spaces affected by the environment. The analysis of the sample revealed forms of the artist’s influence by the natural place: primitive humans used the place as a means of psychological reinforcement, capturing fears through cave paintings. In the art of the ancient Egyptians, the depiction of the place was associated with divinity and holiness. In the arts of Mesopotamian civilizations, the place played a role in shaping human thought. In modern art, the natural place became the psychological space for the artist, leaving an emotional impact and evoking the artist’s emotional memory. The results showed the ability of contemporary artworks to offer new perspectives on the relationship between humans and nature, as well as the diverse media and techniques employed by artists to depict the influence between humans and the natural environment. The research concluded with several recommendations, including the need to enhance the role of art in curricula as a means of understanding the relationship between humans and the environment, and the importance of focusing on supporting artistic projects that reflect environmental and spatial issues due to their impact on raising societal awareness.